Kritik atas Orientalisme dan Kecurigaan atas Kajian Keislaman di Dunia Barat - Subakir, Ahmad (Religió: Jurnal Studi Agama-agama, 2014)
There is always a suspicious view from Moslem intellectual to orientalist’s research and studies on Islamic discourse. The former sees doubtfully that orientalist's research on Islam is fully bias and politically tendentious. William G. Millward observed on this Moslem's suspicion within their books. Moreover, Iranian Moslem intellectuals, according to Millward, tend to be apologetic and emotional. Moslem writers in such situation question the academic authenticity of the orientalists especially in terms of their objective studies on the Quran and the prophet Muhammad. Moslem writers in this regard consider their objectivity toward their finding research that harms Islam in order to Islamic teaching can be returned to the authentic comprehension as believed by the followers. Interestingly, some western intellectuals had also criticized and evaluated the orientalist’s research and studies on Islam. It shows that some of western intellectuals are still implementing the principle of freedom of thought. With this freedom, scholars can deconstruct the negative perspective of the orientalists toward Islamic studies, though such perspectives have crystalized becoming a standard of mainstream thoughts. However, it needs to know that those critics are still suspected having inserted with subjective ideas recalling that religious study is always familiar with an interpretative load and preference.